Positive Effects of an Anti-Aggression and De-Escalation Training on Ward Atmosphere and Subjective Safety May Depend on Previous Training Experience - Fröhlich, Daniela; Rabenschlag, Franziska; Schoppmann, Susanne; Borgwardt, Stefan; Lang, Undine E.; Huber, Christian G. (Frontiers in Psychiatry, 2018)
Anti-aggression and de-escalation (ADE) trainings of healthcare professionals working on psychiatric inpatient wards have been shown to increase staff knowledge and confidence, which could be connected with higher subjective safety. Additionally, a potential reduction of aggressive incidents could improve ward atmosphere. Thus, the current study aimed to investigate the effects of ADE training on ward atmosphere and subjective safety. In 2015, an ADE training was established at the Psychiatric University Clinics (UPK), University of Basel. Nursing staff from 22 wards received theoretical and practical training over the course of five days. Ward atmosphere and subjective safety were assessed using the Essen Climate Evaluation Schema (EssenCES). A total of 46 people had been assessed in 2012 before training implementation (baseline), and 45 persons in 2016 after implementation. In the 2016 group, 23 people had previously participated in an ADE training, and 22 were first-time participants. Patients’ coherence (p = 0.004), subjective safety (p = 0.004), and ward atmosphere (p = 0.001) were rated significantly higher by first-time ADE training participants compared to baseline, and patients’ coherence (p = 0.029) and ward atmosphere (p = 0.011) were rated significantly higher by first-time ADE training participants than by nurses with prior ADE training. There were no significant differences regarding any EssenCES ratings by nurses with prior ADE training compared to baseline. ADE training was exclusively connected with higher ratings on most EssenCES scales for first-time participants. This indicates that the positive effects of ADE training may depend on previous training experience.